1979
DOI: 10.1021/ic50198a023
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and monolayer properties of surfactant tris(2,2'-bipyridine)ruthenium(II) derivatives

Abstract: Die Synthesen der drei Bipyridy1‐Ru(II)‐Komplexe (I)‐(III), die hydrolytisch stabile oberflächenaktive Bindungen und verschiedene Molekülladungen besitzen, sowie die Eigenschaften ihrer monomolekularen Schichten werden beschrieben Der oberflächenaktive Ligand 4,4′‐Di‐n‐nonadecylbipyridin‐(2,2′) wird durch Raney‐ Ni‐Kupplungsreaktion aus 4‐n‐Nonadecylpyridin, Alkylierungsprodukt vom 4‐Methyl‐ pyridin‐Carbanion mit n‐Octadecylchlorid (Ausb. 43%), in l4proz. Ausb. dargestellt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…The lower energy absorptions (455 nm) belong to the Metal-toLigand Charge Transfer ( 1 MLCT) transitions and are typical for the ruthenium trisbipyridine complexes ( = 1.3 10 4 M -1 cm -1 ). The small red shift compared with the unsubstituted bipyridines is due to the slight electron donating effect of the methyl/alkyl groups attached to the thiolate bpy [54,55]. However, the difference in energy is so small that no separate MLCT bands can be detected.…”
Section: Photophysical Properties In Solutionmentioning
confidence: 95%
“…The lower energy absorptions (455 nm) belong to the Metal-toLigand Charge Transfer ( 1 MLCT) transitions and are typical for the ruthenium trisbipyridine complexes ( = 1.3 10 4 M -1 cm -1 ). The small red shift compared with the unsubstituted bipyridines is due to the slight electron donating effect of the methyl/alkyl groups attached to the thiolate bpy [54,55]. However, the difference in energy is so small that no separate MLCT bands can be detected.…”
Section: Photophysical Properties In Solutionmentioning
confidence: 95%
“…In the bulk, block copolymers microphase separate to form materials with discrete morphologies that are dependent upon the temperature, the degree of polymerization, the interaction parameter, χ, and the polymer structure . Similar parameters affect the aggregation behavior of block copolymers in solution studies and at the air−solvent interface using Langmuir−Blodgett techniques . As new functionalized materials become accessible and their phase behavior becomes better understood, numerous applications for these materials are being proposed and developed.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in 1975, Creutz and Sutin 3+ described the oxidation of water by Ru(bpy)3 to produce molecular (4) oxygen. More recently, it has been shown that oxygen can be The synthesis and properties of these complexes have been reported (18) The known Cr(bpy)3C13 was successfully prepared by the oxidation (by rapid exposure to gaseous 02) of Cr(bpy)3C12 (10) However, a number of attempts to synthesize a surfactant chromium byiyridyl complex, either by using mixtures of bpy(C19 H39) 2 and unsubstituted bpy in a similar procedure, or via the (11) preparatio n of [Cr(bpy)2C1 2]Cl followed by insertion of the surfactant ligand, were unsuccessful. Ultimately, our efforts to synthesize the surfactant chromium complex were abandoned.…”
Section: Disclaimermentioning
confidence: 99%
“…Monolayer propertie s of the other surfactan t ruthenium (18) complexes synthesiz ed here have also been surveyed. behavior which is insensitive to changes of counterion.…”
Section: Properties Of Ruthenium Complexes In Monolayers and Micellesmentioning
confidence: 99%